Potensi Akad Mudarabah dalam Kondisi Pandemi Covid-19 di Indonesia - Fageh, Achmad (Akademika, 2020)
There are several government roles in making it a widespread development in the state of Indonesia. Starting from the existence of government agencies that participate and supervise and make rules as a way to sharia economy, to the role of Sharia banks that have been seen its role until in the early 2020 before the presence of Corona viruses that attacked Indonesia. It is evidence that scholars and governments also support the existence of the Mudarabah system in the Sharia economy in Indonesia. Bank Syari'ah Indonesis itself has been awarded as the biggest retail Islamic banking "in the world that owns 1.3 million customers. After that at the end of 2019 once recorded that the customer of sharia bank in Indonesia reaches 31.98 million. This is evidence that people have begun to see the existence of Sharia banks in Indonesia. The role of Mudarabah is very good. Seen from the element of goodness in this system, describing Islam is a beautiful religion in the reflection Relation of Man. It is a great potential to build a nation. Amid the ongoing pandemic that hopefully will be ended soon, then Mudarabah is a solution to keep playing the money to be more productive, mutual help is one of the goodness contained in Mudarabah